Acute intracerebral treatment with amyloid-beta (1–42) alters the profile of neuronal oscillations that accompany LTP induction and results in impaired LTP in freely behaving rats - Kalweit, Alexander Nikolai; Yang, Honghong; Colitti-Klausnitzer, Jens; Fülöp, Livia; Bozsó, Zsolt; Penke, Botond; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2015)
Accumulation of amyloid plaques comprises one of the major hallmarks of Alzheimer’s disease (AD). In rodents, acute treatment with amyloid-beta (Aβ)(1-42) elicits immediate debilitating effects on hippocampal long-term potentiation (LTP). Whereas LTP contributes to synaptic information storage, information is transferred across neurons by means of neuronal oscillations. Furthermore, changes in theta-gamma oscillations that occur during high-frequency stimulation (HFS) to induce LTP predict whether successful LTP will occur. Here, we explored if intra-cerebral treatment with Aβ(1-42) that results in LTP failure, also results in alterations of hippocampal oscillations that occur during HFS of the perforant path-dentate gyrus synapse in 6-month-old behaving rats. HFS resulted in LTP that lasted for over 24h. In Aβ-treated animals, LTP was significantly prevented. During HFS, spectral power for oscillations below 100 Hz (δ,θ,α,β and γ) was significantly higher in Aβ-treated animals compared to controls. In addition, the trough-to-peak amplitudes of theta and gamma cycles were higher during HFS in Aβ-treated animals and the characteristic profiles of theta-gamma oscillations that accompany successful LTP induction were disrupted. These data indicate that alterations in network oscillations accompany Aβ-effects on hippocampal LTP. This may comprise an underlying mechanism through which disturbances in synaptic information storage and hippocampus-dependent memory occurs in AD.